An Investigation Into Operational Risk In Commercial Banks: Empirical Evidence From Nigeria - Zelhuda, Shamsuddin; Olalere Oluwaseyi, Ebenezer; Aminul, Islam; Wan Sallha, Yusoff (2018)
The study was designed to explore operational risk in banking industry. The study identified that existing studies are sketchy in developing economies while most studies are largely theoretical and have lesser empirical evidence. Data on audited financial reports of selected sixteen (16) commercial banks over the period of 2009 to 2015 have been collected making up to 112 observations. Panel data approach is employed in the study for the analytical model which run Hausman test for random or fixed effect choice and hypothesis testing. The firm performance is measured by net interest margin while operational risk is proxy by cost to income and total operating expenses to total assets ratio. The controlled variables used in this study include bank size and GDP growth rate. Based on the random effect analysis in the model, bank efficiency ratio (ER) has a negative significant effect on firm performance, suggesting that the lower cost to income ratio, is the better the bank performance in terms of Net Interest Margin. Operating expenses ratio has a positive significant effect on firm performance. The firm size is not an important determinant to the firm performance of commercial banking sector in Nigeria, as compared to operational risk. GDP play an important role the performance of commercial banks during the period of study. Hence, this paper contributes to the understanding of the dynamic nature of operational risk and suggest that further study can explore the effects of operational risks on banks efficiency using wider time-frame.